Time Overrun in Construction Project - Othman, I. (Institute of Physics Publishing, 2018)
Timely completion is the key criteria to achieve success in any project despite the industry. Unfortunately construction industry in Malaysia has been labelled as industry facing poor performance leading to failure in achieving effective time management. As the consequence most of the project face huge amount of time overrun. This study assesses the causes of construction projects time overrun in Malaysia using structured questionnaire survey. Each respondent is asked to assign a one-to-five rating for each of the 18 time factors identified from literature review. Out of the 50 questionnaires sent out, 33 were received back representing 68 of the response rate. Data received from the questionnaires were analysed and processed using the descriptive statistics procedures. Findings from the study revealed that design and documentation issues, project management and contract administration, ineffective project planning and scheduling, contractor's site management, financial resource management were the major factors that cause the time overrun. This study is hoped to help the practitioners to implement the mitigation measure at planning stage in order to achieve successful construction projects. Â© Published under licence by IOP Publishing Ltd.